Assessment of Permeable Pavements for Urban Flood Mitigation and Community Resilience - Mohamad, Dadang (International Journal of Science and Society, 2024)
Urban flooding is a significant challenge in many developing cities, adversely impacting community resilience and infrastructure stability. This study investigates the use of permeable pavements as a sustainable solution for urban flood mitigation and enhancement of community resilience. The research focuses on the engineering design and drainage efficiency of permeable pavements, evaluating their effectiveness in reducing surface runoff and preventing waterlogging. A mixed-methods approach was employed, combining quantitative data from hydrological simulations and qualitative insights from stakeholder interviews. The findings reveal that permeable pavements significantly reduce surface runoff, thereby mitigating urban flooding and enhancing drainage efficiency. Additionally, the study highlights the community benefits, including improved water quality, reduced heat island effect, and enhanced aesthetic value of urban spaces. Despite the initial higher costs and maintenance requirements, the long-term benefits of permeable pavements make them a viable solution for sustainable urban development. This research provides actionable recommendations for urban planners, engineers, and policymakers to incorporate permeable pavements into urban infrastructure projects, promoting resilience and sustainability in urban communities.